Zebra dolomites of the Spessart, Germany: implications for hydrothermal systems of the European Zechstein Basin - Kelka, Ulrich; Beaudoin, Nicolas E.; Lorenz, Joachim; Köhn, Daniel; Regenauer-Lieb, Klaus; Boyce, Adrian; Chung, Peter (International Journal of Earth Sciences, 2023)
Zebra dolomites have a distinctive texture and are a peculiar structural variety of dolostones often encountered in the vicinity of base metal deposits commonly in the Mississippi Valley-Type (MVT). We investigate origin and evolution of the zebra dolomites found in the region of the Spessart, northwestern Bavaria, Germany, through diagenetic and petrogenetic analysis using SEM, CL microscopy, O–C isotopes, and fluid inclusion micro-thermometry. Here, we aim to shed light on the nature of the fluids that altered the zebra dolomite of the Zechstein formation. We distinguish the geochemical signatures of two different fluid flow regimes post-dating texture formation, each characterized by specific homogenization temperatures and oxygen–carbon isotope ratios (Event 1: T h = 120 °C; δ 18 O fluids = [0 to 2‰]; Event 2; T h = 300 °C; δ 18 O fluids = 18‰). Comparison of these fluids and the associated mineralization with published regional fluid flow data support that the zebra dolomites in the Spessart most likely coincided with the Permian large-scale fluid flow event that occurred throughout the European Zechstein Basin. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-11-17
Keywords: Dedolomitization; Dolomitization; Hydrothermal systems; Spessart; Zebra dolomites